2007
DOI: 10.1111/j.1540-8167.2007.00833.x
|View full text |Cite
|
Sign up to set email alerts
|

Bepridil Reverses Atrial Electrical Remodeling and L‐Type Calcium Channel Downregulation in a Canine Model of Persistent Atrial Tachycardia

Abstract: Bepridil reverses the electrophysiological consequences of atrial remodeling to some extent and L-type calcium channel downregulation in a canine model of atrial tachycardia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 37 publications
4
40
2
Order By: Relevance
“…In the LA site, SCN5A and Cx43 were also downregulated in the pacing control group, but the changes in the LCC and Kv4.3 did not show any statistical significance, but they showed similar tendencies as in the RA site. In the bepridil group, the downregulation of the LCC and SCN5A was suppressed in the RA, similar to a previous report, 10 but not in the LA. The downregulation of Kv4.3 and Cx43 was not affected by bepridil administration.…”
Section: Circulation Journal Vol72 February 2008supporting
confidence: 90%
See 1 more Smart Citation
“…In the LA site, SCN5A and Cx43 were also downregulated in the pacing control group, but the changes in the LCC and Kv4.3 did not show any statistical significance, but they showed similar tendencies as in the RA site. In the bepridil group, the downregulation of the LCC and SCN5A was suppressed in the RA, similar to a previous report, 10 but not in the LA. The downregulation of Kv4.3 and Cx43 was not affected by bepridil administration.…”
Section: Circulation Journal Vol72 February 2008supporting
confidence: 90%
“…Most recently,(LCC), but they did not document any difference between the right and left atrium (RA and LA). 10 Because we have demonstrated an inhomogeneity of electrical remodeling in the RA and LA, at least in our canine rapid atrial stimulation model without atrioventricular block, 11,12 in the present study we focused on the effect of bepridil on atrial electrical remodeling and the difference between the RA and LA in using a new protocol in which we started administering the drug in the later phase of the pacing protocol.…”
mentioning
confidence: 98%
“…Especially, bepridil has a concentration-dependent strong I CaL blocking effect. [16][17][18][19] Nishida et al reported the efficacy of bepridil against the expression of L-type calcium channel 1c messenger ribonucleic acid (mRNA) after 6 weeks of rapid atrial pacing. 16) 1c mRNA expression was decreased in only the rapid pacing group.…”
Section: Mechanisms Of Atrial Electrical Remodeling In the Acute Phasementioning
confidence: 99%
“…[16][17][18][19] Nishida et al reported the efficacy of bepridil against the expression of L-type calcium channel 1c messenger ribonucleic acid (mRNA) after 6 weeks of rapid atrial pacing. 16) 1c mRNA expression was decreased in only the rapid pacing group. By using bepridil, it was maintained signifi- Rapid pacing decreased atrial ERPs in all regions significantly (P < 0:05).…”
Section: Mechanisms Of Atrial Electrical Remodeling In the Acute Phasementioning
confidence: 99%
“…8) In addition to these electrophysiological actions, it has been speculated in a few reports that bepridil might affect the myocardial remodeling that would promote the arrhythmogenic substrates in a condition of long-lasting AF, and the recovery of down-regulated ion channels was induced by bepridil treatment at least in several experimental studies. 9,10) Regardless of the validity of the proposed anti-remodeling effect of bepridil, several reports have confirmed that it sometimes takes a relatively long time for bepridil to interrupt long-lasting AF even in effective cases. Additionally, bepridil therapy could be associated with risk of adverse effects such as torsades de pointes, QT prolongation, or bradycardia.…”
mentioning
confidence: 99%